Chikungunya viruses containing the A226V mutation detected retrospectively in Cameroon form a new geographical subclade. (December 2021) - Agbodzi, Bright; Yousseu, Francine Berlange Sado; Simo, Fredy Brice Nemg; Kumordjie, Selassie; Yeboah, Clara; Mosore, Mba-Tihssommah; Bentil, Ronald E.; Prieto, Karla; Colston, Sophie M.; Attram, Naiki; Nimo-Paintsil, Shirley; Fox, Anne T.; et al.
Highlights: Chikungunya viruses (CHIKVs) in Cameroon form a new geographical subclade. Cameroon CHIKVs contain the A226V mutation. Cameroon CHIKVs have an evolutionary rate two times that of the main East/Central/South African (ECSA). CHIKVs in Yaoundé and surrounding areas are likely Aedes albopictus -adapted. Abstract: Background: Chikungunya virus (CHIKV) is a re-emerging arbovirus associated with sporadic outbreaks in Cameroon since 2006. Viral whole genomes were generated to analyze the origins of evolutionary lineages, the potential of emergence/re-emergence, and to infer transmission dynamics of recent Cameroon CHIKV outbreak strains. Methods: Samples collected between 2016 and 2019 during CHIKV outbreaks in Cameroon were screened for CHIKV using reverse transcription PCR (RT-PCR), followed by whole genome sequencing of positive samples. Results: Three coding-complete CHIKV genomes were obtained from samples, which belong to an emerging sub-lineage of the East/Central/South African genotype and formed a monophyletic taxon with previous Central African strains. This clade, which we have named the new Central African clade, appears to be evolving at 3.0 × 10 −4 nucleotide substitutions per site per year (95% highest posterior density (HPD) interval of 1.94 × 10 −4 to 4.1 × 10 −4 ). Notably, mutations in the envelope proteins (E1-A226V, E2-L210Q, and E2-I211T), which are known to enhance CHIKV adaptability and infectious potential in Aedes albopictus, were present in all strains and mapped to established high-density Ae. albopictus populations. Conclusions: These new CHIKV strains constitute a conserved genomic pool of an emerging sub-lineage, reflecting a putative vector host adaptation to Ae. albopictus, which has practically displaced Aedes aegypti from select regions of Cameroon.